Qualidade dos frutos de lichia submetidos a diferentes temperaturas de armazenamento - Ramos, Dayana Portes [UNESP]; Leonel, Sarita [UNESP]; Evangelista, Regina Marta [UNESP]; Silva, Cristiano Pereira da [UNESP]; Nina, José Antonio Della [UNESP] (My University, 2011)
The lychee (Litchi chinensis Sonn.) is considered as the queen of the fruits due to its excellent flavor, aroma and fragrance. However, it has great losses in the post-harvest. One of the options to reduce these losses would be to use the ideal storage temperature. Thus, the objective of this work was to verify the effect of different temperatures in the preservation post-harvest of 'Bengal' lychee fruits. The fruits were harvested of the orchard of the orchard of the FCA/UNESP, in Botucatu city, São Paulo state, Brazil. Fruits were taken to laboratory, where the fruits were selected and immersed in 200 mg L sodium hypochlorite for 10 minutes. After the drying in the air the fruits were packed in expanded polystyrene trays and wrapped polyvinyl chloride film. Later the fruits were stored in oxygen demand biological (BOD) at the following temperatures: 0; 2,5 and 5 °C. The analyses of fresh mass loss, pH, titratable acidity, soluble solids, ratio, reducing sugars, total reducing sugars, non-reducing sugars and vitaminC were carried out every four days, up to the 12º day. The experimental design used was completely randomized. The results showed that the fruits kept at 0 ºC had lower values of fresh mass loss. There was no significant difference in pH, soluble solids and reducing sugars. There was a decrease of the vitamin C values during the preservation period, regardless of the storage temperature used and the fruits kept at 5 ºC showed the highest values in the 4 and 8 day of storage.

Alichia (Litchi chinensis Sonn.) é considerada como a rainha das frutas pelo seu excelente sabor, aroma e fragrância; porém ocorrem grandes perdas na pós-colheita.Umadas opções para reduzir essas perdas seria usar a temperatura ideal de armazenamento. Assim sendo, o objetivo desse trabalho foi verificar o efeito de diferentes temperaturas de armazenamento na conservação pós-colheita de frutos de lichia 'Bengal'. Os frutos foram colhidos do pomar da Faculdade de Ciências Agronômicas da Universidade Estadual de São Paulo, campus de Botucatu e levados para o laboratório, onde foram selecionados e imersos em hipoclorito de sódio 200 mg L por 10 minutos. Após a secagem ao ar os frutos foram acondicionados em bandejas de poliestireno expandido e envolvidos em filme de policloreto de vinila (PVC), armazenados em demanda biológica de oxigênio (DBO) nas temperaturas de 0; 2,5 e 5°C.As análises de perda de massa fresca, pH, acidez titulável, sólidos solúveis, SS/AT, açúcar redutor, açúcar não redutor, açúcar total e vitamina C foram realizadas a intervalos de quatro dias, até o 12º dia. O delineamento experimental foi o inteiramente casualizado. Os resultados mostraram que os frutos mantidos a 0 ºC apresentaram menores teores de perda de massa fresca. Não houve diferenças significativas para pH, sólidos solúveis e açúcar redutor. Houve diminuição do teor de vitamina C, durante o período de conservação, independente da temperatura de armazenamento utilizada, sendo que os frutos mantidos a 5ºC apresentaram maiores teores no 4º e 8º dia de armazenamento.
Lychee fruits of quality exposed to different storage temperatures
Keywords: Litchi chinensis; Refrigeration; Postharvest; Litchi chinensis; Refrigeração; Pós-colheita